Relıgıosıty, Local Wısdom, And Socıal Psychology - Winarno Heru Murjito; Arif Julianto Sri Nugroho; Sigit Adhi Pratomo; Jarot Prasetyo; Ike Anisa; Tasari Tasari (Cita Konsultindo Research Center, 2024)
This research aims to conduct a multivariate test of the dependent variable on the intention of learning Unwidha’s students for Social Psychology are influenced by two independent variables, namely religiosity and local genius values. The research object as the sample is students from Department of Psychology Universitas Widya Dharma around 100 respondents with purposive sampling technique. The data analysis in this research is in the form of reliability and validity tests of items, and variable correlation tests which are useful for providing a map of perception in the people's mind regarding the proof of intention of students for learning Social Psychology. Quantitative multivariate test using The AMOS Software. The test results found that the religiosity and local genius values variables are proof which influenced the intention of learning, From the research findings of the model evidence, a strategy is needed for stakeholders to develop human resources strategies towards the competitive advantage of departement of Psychology towards to increase for students motivation for Social Psychology learning.